Strategi Penguatan Resiliensi Usaha Budidaya Lobster Air Tawar di Kabupaten Nganjuk Berbasis Analisis Keberlanjutan Multidimensi: Strategi Penguatan Resiliensi Usaha Budidaya Lobster Air Tawar di Kabupaten Nganjuk Berbasis Analisis Keberlanjutan Multidimensi - Fatahul Haqqi, Muhammad; Setyadi, Taufik; Roidah, Ida Syamsu (JURNAL MANAJEMEN MOTIVASI, 2026)
This study assesses the sustainability of freshwater lobster aquaculture in Nganjuk Regency using income analysis, RAPFISH, and the Analytic Network Process (ANP). Although economically feasible, the sector faces limited market access, long cultivation periods, low policy priority, and uneven farmer capacity. RAPFISH results indicate a less sustainable status and identify key sensitive attributes through leverage analysis. ANP prioritization recommends enhancing human resources, expanding markets, adopting semi-intensive technologies, strengthening institutions and partnerships, and promoting environmentally friendly practices. These findings offer integrated insights to support policy formulation and sustainable aquaculture development. Keywords: Sustainability Strategy; Freshwater Lobster; Rapfish; ANP